2016
DOI: 10.1080/21645515.2016.1176652
|View full text |Cite|
|
Sign up to set email alerts
|

Intradermal vaccination for infants and children

Abstract: Intradermal (ID) vaccination induces a more potent immune response and requires lower vaccine doses as compared with standard vaccination routes. To deliver ID vaccines effectively and consistently, an ID delivery device has been developed and is commercially available for adults. The clinical application of ID vaccines for infants and children is much anticipated because children receive several vaccines, on multiple occasions, during infancy and childhood. However, experience with ID vaccines is limited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
7
0
1
Order By: Relevance
“…Second, improved or alternative methods of administering vaccines should be considered. Recent studies have shown that a potent immune response can be induced by intradermal vaccination, and that dose-sparing can be achieved [118]. To date, no Hib vaccine has been evaluated for intradermal administration, although the advantages and potential downsides of this delivery method have been discussed [119].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Second, improved or alternative methods of administering vaccines should be considered. Recent studies have shown that a potent immune response can be induced by intradermal vaccination, and that dose-sparing can be achieved [118]. To date, no Hib vaccine has been evaluated for intradermal administration, although the advantages and potential downsides of this delivery method have been discussed [119].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Les premières reposent sur des systèmes sans aiguille [37]. Cette voie d'administration permet par ailleurs de limiter la quantité d'antigène nécessaire pour obtenir une réponse immunitaire similaire à la voie IM, ce qui a pu être constaté dans de nombreuses études menées notamment chez l'enfant [38]. Certains dispositifs sont utilisables avec les formats de vaccin existants (flacons ou ampoules), d'autres font partie intégrante du vaccin lui-même (vaccins à délivrance muqueuse).…”
Section: Les Nouvelles Méthodes De Délivrance Des Vaccinsunclassified
“…These DCs efficiently take up and present antigens, thereby eliciting innate and adaptive immune responses . In addition, ID vaccination requires less vaccine to induce strong prophylactic responses compared to SC and IM routes, suggesting significant dose‐sparing and cost‐saving benefits …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, ID vaccination requires less vaccine to induce strong prophylactic responses compared to SC and IM routes, suggesting significant dose-sparing and cost-saving benefits. [13][14][15][16] Despite the immunological and economic advantages, ID administration using conventional needles and syringes shows technical difficulties. To overcome such drawbacks, easy-to-use delivery devices have been introduced, including an adapter for existing needles and syringes, a microneedle and a needle-free jet injector.…”
mentioning
confidence: 99%